Variação da Evapotranspiração da Floresta Nacional do Tapajós para Anos de El niño e La niña (2000-2003) - Aguiar, Diego R.; Machado, Wilderclay; Tapajós, Raphael; Oliveira Jr., Raimundo C.; da Silva, Rodrigo; Júnior, Miércio (Ciência e Natura, 2011)
.